Phenolic Composition and Skin-related Properties of the Aerial Parts Extract of Different Hemerocallis Cultivars - Katarzyna Szewczyk; Małgorzata Miazga-Karska; Wioleta Pietrzak; Łukasz Komsta; Barbara Krzemińska; Anna Grzywa-Celińska (MDPI AG, 2020)
Hemerocallis plants are important vegetables with nutritional and health value, especially in eastern Asia, where they have been used as medicines to cure disease such as depression and inflammation for thousands of years. The present study concerns the determination of flavonoids and phenolic acids, as well as antioxidant, anti-collagenase, anti-elastase, anti-tyrosinase and antimicrobial properties of taxa cultivated in Poland. For chemical composition estimation, LC-ESI-MS/MS analysis and spectrophotometric assays were performed. The results show the presence of sixteen compounds in all analyzed species. Among the investigated cultivars, it was found that H. "Chicago Apache" and H. fulva var. kwanso have the highest total phenolic acid and flavonoid content. The most abundant compounds in all analyzed extracts were chlorogenic acid (209.8 to 1010.0 µg/g of DE) and quercetin-3-O-rutinoside (114.7 to 1049.7 µg/g of DE). The studied extracts exhibited moderate to high skin-related activities. These properties were correlated with a high concentration of polyphenols. The present study demonstrated that Hemerocallis cultivars contain significant amounts of phenolic compounds with good skin-related activities and could be interesting as novel sources of bioactive agents for the pharmaceutical, food and cosmetic industries.